1998
DOI: 10.1007/s003390051284
|View full text |Cite
|
Sign up to set email alerts
|

STM study of room temperature adsorption of Au on the Si(111)(7×7) surface: evidence for the reaction of Au atoms with Si rest atoms

Abstract: The initial stages of Au adsorption at sub-monolayer coverages on the Si(111)-(7×7) surface at room temperature have been studied by scanning tunneling microscopy (STM). At very low Au coverages (Θ ∼ 0.01 monolayers) STM images show that some of the triangular sub-unit cells have slightly larger apparent height. These peculiar features are interpreted as being caused by the redistribution of charge in the 7 × 7 unit cell following the adsorption of Au atoms on Si rest atom sites. STM images suggest that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, from previous experimental studies the adsorption sites and the nature of the bonds between these metallic atoms and Si111-7 7 surface remain elusive [5][6][7][8][9]. Scanning tunneling microscopy (STM) is a powerful tool in surface study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, from previous experimental studies the adsorption sites and the nature of the bonds between these metallic atoms and Si111-7 7 surface remain elusive [5][6][7][8][9]. Scanning tunneling microscopy (STM) is a powerful tool in surface study.…”
mentioning
confidence: 99%
“…While it is often used to observe the adsorption of metallic atoms, the identification of adsorption sites remains nontrivial since STM only measures the local density of states near the Fermi level rather than the metallic atoms themselves [10]. Previous STM studies showed that at low coverage both Ag and Au form similar triangular patterns on Si111-7 7 at room temperature [6][7][8][9]. While the triangular STM image for Ag was identified as due to a single Ag atom by correlating to the quantitative Ag dosage [6,7], the triangular STM image for Au was speculated as due to a cluster of three Au atoms, each adsorbing at a rest Si atom site within the half unit cell [9].…”
mentioning
confidence: 99%
“…Quite unexpectedly, when there is just one single Au, Ag, or Cu atom occupying the faulted half unit cell, the STM images show up as six bright (brighter than Si adatoms) spots that form a triangle. Previously, these triangular patterns were often assigned as clusters formed by three or six atoms [21,22]; our STM images taken at low temperature (LT) [ Fig. 2(d)] clearly show that only a single bright spot remains in the faulted half unit cell after cooling to 77 K. This change in STM images between RT and LT is found reversible, indicating that the six bright spots at RT is a result of frequent hopping of an atom among different adsorption sites.…”
mentioning
confidence: 99%
“…24 However, from previous experimental studies the adsorption sites and the nature of the bonds between these metallic atoms and the Si(111)-7 × 7 surface remain elusive. [25][26][27][28] Our results indicate that the dangling bonds at Si rest atom and the Si adatom, either at the corner or at the centre, are not the perfect adsorption sites for Au 1 and Ag because their adsorption energies are higher than those on the high coordination sites. The above results can be directly compared to a recent first principles study by Cho and Kaxiras 21 22 for K, Mg, Ga, Si and Ge, using a (4 × 4) supercell rather than a full (7 × 7) cell.…”
Section: Resultsmentioning
confidence: 94%